HOFFMAN INDEX OF MANIFOLDS - Naaum, Adil; Sadek, Afraa (Iraqi Journal of Science, 2024)
For a connected topological space M we define the homeomorphism and period noncoincidence indices of M, each of them is topological invariant reflecting the abundance of fixed point free self homeomorphisms and periodic point free self maps defined on M respectively.We give some results for computing each of these indices and we give some examples and some results relating these indices with Hoffman index.